Preparation method and application of photocuring 3D printing AlN-based ultrathin precise porous structure ceramic
Preparation of AlN-based ultra-thin precision porous ceramics through photocuring 3D printing, solving the problem of difficult control of thermal uniformity and flatness in the production of high-precision chips, and achieving high-precision, defect-free ceramic printing and temperature uniformity to meet the needs of cutting-edge technology environment.
Patent Information
- Application Number
- CN202411219981.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-02
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-02
AI Technical Summary
Existing electrostatic chucks are difficult to achieve thermal uniformity and flatness while controlling thermal uniformity during high-precision chip production. Especially in cutting-edge technology environments, temperature control and flatness requirements for AlN materials caused by high thermal conductivity and thermal expansion coefficient. Difficult to satisfy.
Photocuring 3D printing is used to prepare AlN-based ultra-thin precision porous ceramics. By preparing aluminum nitride photocuring slurry, including aluminum nitride powder, photocuring resin, dispersant, photoinitiator, sintering aid and defoaming agent, And it is printed by a multi-material photocuring 3D printer, and after degreasing and sintering, a porous ceramic structure with high thermal conductivity and adjustable air flow is produced.
While improving thermal uniformity and flatness in the electrostatic chuck, high-precision, defect-free AlN-based ultra-thin porous ceramics are printed to meet the temperature control requirements in cutting-edge technical environments.
Smart Images

Figure CN119263848A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ceramic additive manufacturing, and specifically relates to a preparation method and application of photocuring 3D printing AlN-based ultra-thin precision porous structure ceramics. Background Art
[0002] Electrostatic chuck is a fixture that uses the principle of electrostatic adsorption to clamp and fix the adsorbed object. It is suitable for vacuum and plasma environments. Its main function is to adsorb ultra-clean thin sheets (such as silicon wafers) and keep the adsorbed object at a good flatness. It can suppress the deformation of the adsorbed object during the process and can also adjust the temperature of the adsorbed object. Electrostatic chuck is widely used in the semiconductor core manufacturing process and is one of the core components of key processes such as ion implantation, etching, and vapor deposition. Especially in the indispensable vapor deposition link in the chip production process, this link has high requirements for the overall thermal uniformity and flatness of the disk body. The temperature difference of the entire disk body must not exceed 5% to ensure the thickness of the deposited layer is consistent. At this stage, the disk body is mostly heated by buried wires combined with the design of airflow holes. Helium is filled in the through holes to circulate to assist in ensuring the thermal uniformity of the disk body. In the working environment of cutting-edge technology (such as photolithography machines, etc.), the temperature control and flatness of the electrostatic chuck disk body are extremely high.
[0003] Due to the high thermal conductivity and thermal expansion coefficient of AlN, aluminum nitride is regarded as an ideal material for the next generation of semiconductor packaging. This patent proposes a method of preparing an ultra-thin, precise, porous structured ceramic based on AlN for an electrostatic chuck by photocuring 3D printing, which can be placed in the airflow holes on the surface of the electrostatic chuck. The main reason for selecting aluminum nitride is that it has a high thermal conductivity, which is beneficial to promoting the overall thermal uniformity of the chuck. Moreover, in this invention, the aluminum nitride porous ceramic can control the airflow by controlling the pore structure and quantity of the porous ceramic, thereby further adjusting the overall thermal uniformity and flatness of the electrostatic chuck. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to improve the deficiencies in the prior art and provide a method for preparing ultra-thin precision porous structure ceramics based on AlN by photocuring 3D printing.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing ultra-thin precision porous structure ceramics based on AlN by photocuring 3D printing, characterized in that: comprising:
[0008] Preparing aluminum nitride photocurable slurry, wherein the aluminum nitride ceramic slurry comprises aluminum nitride powder, photocurable resin, dispersant, photoinitiator, sintering aid and defoamer;
[0009] Among them, calculated by mass percentage, aluminum nitride powder: 50% to 73%, photocurable resin: 20% to 30%, dispersant: 1% to 5%, photoinitiator: 2% to 5%, sintering aid: 3% to 8%, defoamer: 1% to 2%;
[0010] The above-mentioned aluminum nitride photocurable slurry is added into the slurry chamber of a multi-material photocurable 3D printer, and the model information of the aluminum nitride porous ceramic skeleton is input into the printer for photocurable printing. After degreasing, decarburization and sintering, the photocurable 3D printed AlN-based ultra-thin precision porous structure ceramics are obtained.
[0011] The photo-preparation method as described in claim 1 is characterized in that: the photocurable resin is a mixture of a monofunctional photocurable monomer, a difunctional photocurable monomer, a tetrafunctional photocurable monomer and a high refractive index photocurable monomer; wherein the volume ratio of the monofunctional photocurable monomer, the difunctional photocurable monomer and the tetrafunctional photocurable monomer is 5:3:2.
[0012] As a preferred embodiment of the preparation method of the present invention, the monofunctional photocurable monomer is o-phenylphenoxyethyl acrylate; the difunctional photocurable monomer is 1,6-hexanediol diacrylate; and the tetrafunctional photocurable monomer is ethoxylated pentaerythritol tetraacrylate.
[0013] As a preferred embodiment of the preparation method of the present invention, the dispersant is a polymer copolymer dispersant, the defoamer is defoamer 204, the photoinitiator is bis(2,4,6-trimethylbenzoyl)diphenylphosphine oxide, and the sintering aid is yttrium trioxide powder.
[0014] As a preferred embodiment of the preparation method of the present invention, the preparation method of the aluminum nitride slurry includes adding anhydrous ethanol to aluminum nitride powder, photocurable resin, dispersant, photoinitiator, sintering aid and defoaming agent and placing them in a ball mill, using zirconium oxide ball milling beads as ball milling media, and after ball milling, placing the mixture in a drying oven for drying and then grinding through a 100-mesh sieve to obtain a mixed powder with an average particle size of 2.5 μm.
[0015] As a preferred embodiment of the preparation method of the present invention, the aluminum nitride powder is mixed with the sintering aid yttrium oxide powder in a ratio of 95:5.
[0016] As a preferred embodiment of the preparation method of the present invention, the predetermined rotation speed of the ball mill is 350 rpm, the predetermined time of the ball mill is 10 h ± 0.5 h, the predetermined temperature of the drying box is 80 ° C, the predetermined time of the drying box is 6 h, the average particle size of the aluminum nitride powder is 1.8 to 2 μm, and the average particle size of the yttrium oxide powder is 50 nm.
[0017] As a preferred embodiment of the preparation method of the present invention, the degreasing process of the aluminum nitride porous ceramic embryo adopts a protective atmosphere, and the protective atmosphere adopts nitrogen; the aluminum nitride porous ceramic embryo is placed in a central ring tube furnace, the degreasing temperature is from 25°C to 600°C, the heating rate is 0.1°C / min to 1°C / min, and the temperature is kept at 150°C, 250°C, 350°C and 450°C for 60 to 240 minutes respectively;
[0018] The exposure intensity of the photocuring printing process is 30mW / cm 2 ; The printing layer thickness is 20μm; The exposure time is 4s; After printing layer by layer, an aluminum nitride porous structure ceramic embryo is obtained.
[0019] As a preferred embodiment of the preparation method of the present invention, the degreased aluminum nitride porous ceramic embryo is subjected to decarburization treatment and placed in a low-temperature muffle furnace. The decarburization temperature is from 25°C to 700°C, the heating rate is 0.5°C / min to 5°C / min, and the temperature is kept at 400°C and 700°C for 60 minutes respectively.
[0020] The high temperature sintering is pressureless sintering or gas pressure sintering; the high temperature sintering adopts a protective atmosphere, and the protective atmosphere generally adopts inert gas nitrogen; the high temperature sintering temperature is 1800-1850° C., and the heat preservation is 4-5 hours.
[0021] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing photocurable 3D printed AlN-based ultra-thin precision porous structural ceramics, and to use the photocurable 3D printed ultra-thin precision AlN porous structural ceramics in an electrostatic chuck.
[0022] Beneficial effects of the present invention:
[0023] The present invention adopts a new photosensitive resin active diluent formula, o-phenylphenoxyethyl acrylate: 1,6-hexanediol diacrylate: ethoxylated pentaerythritol tetraacrylate is 5:3:2, to prepare light-cured printing slurry, which improves the curing depth of light-cured 3D printing AlN ceramic slurry and reduces the viscosity of AlN ceramic slurry, which is conducive to the rapid printing of high-precision, defect-free AlN-based ultra-thin precision porous structure ceramic blanks. Further, combined with the reasonable selection of sintering temperature, the present invention can obtain AlN-based ultra-thin precision porous structure ceramics for electrostatic chucks, which can improve the flatness of the electrostatic chuck body by controlling the air flow while ensuring the thermal uniformity of the electrostatic chuck body. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments and comparative examples. Obviously, the drawings described below are only some embodiments and comparative examples of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0025] Figure 1 The morphology of a complete precision ceramic green embryo sample obtained after photocuring printing of the aluminum nitride slurry prepared in Example 1 of the present invention.
[0026] Figure 2 This is the morphology of the ceramic green body sample obtained after photocuring printing using a slurry prepared with different resins in the same proportion as in Example 1 in Comparative Example 1 of the present invention.
[0027] Figure 3 This is the morphology of the ceramic green body sample obtained after light-curing printing using a slurry prepared with different resins in the same proportion as in Example 1 in Comparative Example 2 of the present invention.
[0028] Figure 4 This is the morphology of the ceramic green body sample obtained by photocuring printing with a slurry prepared with different resins in the same proportion as in Example 1 in Comparative Example 3 of the present invention.
[0029] Figure 5 This is the morphology of the ceramic green body sample obtained by photocuring printing with a slurry prepared with different resins in the same proportion as in Example 1 in Comparative Example 4 of the present invention.
[0030] Figure 6 This is the morphology of the ceramic green body sample obtained after photocuring printing using a slurry prepared with different resins in the same proportion as in Example 1 in Comparative Example 5 of the present invention.
[0031] Figure 7This is the morphology of the ceramic green body sample obtained by photocuring printing with a slurry prepared with different resins in the same proportion as in Example 1 in Comparative Example 6 of the present invention.
[0032] Figure 8 The viscosity of three different resin formulations of the same proportion in Example 1 and Comparative Examples 1, 2, and 3 is compared.
[0033] Fig. 9 This is a viscosity comparison of the same proportion of three different resin formulations in Comparative Examples 4, 5, and 6.
[0034] Fig.10 This is the precise structure obtained after sintering at 1850°C in Example 1.
[0035] Fig.11 This is the SEM image of Example 1 after sintering at 1850°C.
[0036] Fig.12 This is the SEM image of Example 1 after sintering at 1800°C. DETAILED DESCRIPTION
[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0038] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0039] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0040] Unless otherwise specified, the raw materials used in the present invention are all commonly available in the market in this field, and the details are shown in Table 1.
[0041] The 3D printer used in this invention is the MicroArch S230A micro-nano ceramic 3D printer developed by BMF Percision Tech. The thickness of the ceramic printing layer used for testing is 20 μm, and the exposure energy is 30 mW / cm 2 , the exposure time is 4s.
[0042] Table 1
[0043]
[0044] Example 1
[0045] This embodiment provides a method for preparing ultra-thin precision AlN porous structure ceramics by photocuring 3D printing, specifically:
[0046] 1) Preparation of aluminum nitride photocuring slurry:
[0047] Weigh 8.46g of monofunctional photosensitive resin active diluent o-phenylphenoxyethyl acrylate, 5.08g of difunctional photosensitive resin active diluent 1,6-hexanediol diacrylate, 3.38g of tetrafunctional photosensitive resin active diluent ethoxylated pentaerythritol tetraacrylate, 1g of photoinitiator phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, 0.7g of defoamer 204, 47.5g of aluminum nitride powder and 2.5g of yttrium trioxide sintering aid, and 1g of dispersant SP-710 in a plastic jar, add 20g of zirconium oxide ball milling beads, and ball mill at 350 rpm for 10 hours to obtain a photocurable slurry.
[0048] 2) Perform light-curing 3D printing:
[0049] The micro-nano ceramic printer MicroArch S230A (Magic Cube Precision Technology Co., Ltd.) was used, with an exposure intensity of 30mW / cm 2 , single exposure time 4 seconds, single layer thickness 20 microns, printed cubic porous ceramic samples with wall thickness of 120μm, 90μm and 60μm respectively. The printed parts were ultrasonically cleaned twice with anhydrous ethanol, each time for 1 min.
[0050] See the photo of the printed ceramic body for details. Figure 1 , the wall thickness is uniform and there are no obvious cracks, indicating that the printing result is good.
[0051] 3) Degreasing:
[0052] The printed body is degreased by a two-step degreasing method. The specific steps are as follows: Place the printed sample in a boron nitride crucible, place the crucible in a tube furnace, and perform degreasing. The first step is low-temperature degreasing. First, the temperature is raised from room temperature to 250°C at a heating rate of 1°C / min in a nitrogen atmosphere, and then kept at 150 and 250°C for 1h, and then cooled to room temperature. The second step is high-temperature degreasing. The temperature is raised to 250°C at a heating rate of 1°C and kept for 1h, and then raised to 600°C at a heating rate of 0.1°C / min, and kept at 350 and 450°C for 1h and 4h, respectively, and cooled to room temperature.
[0053] 4) Sintering
[0054] After debinding, sintering is carried out in a nitrogen atmosphere at a sintering temperature of 1850°C and a holding time of 5 hours.
[0055] like Fig.10 , 11 As shown, a relatively complete precision structure and microstructure are obtained after sintering.
[0056] Comparative Example 1
[0057] The relationship between the curing depth and the exposure energy was tested by using other different resin formulas. A slurry with a mass fraction of 50% of AlN photocurable printing ceramic slurry was prepared, and the proportions of other additives were the same as in Example 1. The resin formula used N-acryloylmorpholine, 1,6-hexanediol diacrylate and ethoxylated pentaerythritol tetraacrylate in a ratio of 5:3:2. Figure 2 As shown, it is difficult to achieve a high curing depth at a low exposure intensity and to achieve effective photocuring with the AlN paste using this resin formulation.
[0058] Comparative Example 2
[0059] The relationship between the curing depth and the exposure energy was tested by using other different resin formulas. A slurry with a mass fraction of 50% of AlN photocuring printing ceramic slurry was prepared, and the proportions of other additives were the same as in Example 1. The resin formula used propoxylated neopentyl glycol acrylate, 1,6-hexanediol diacrylate and ethoxylated pentaerythritol tetraacrylate in a ratio of 5:3:2. Figure 3 As shown, it is difficult to achieve a high curing depth at a low exposure intensity and to achieve effective photocuring with the AlN paste using this resin formulation.
[0060] Comparative Example 3
[0061] The relationship between the curing depth and the exposure energy was tested by using other different resin formulas. A slurry with a mass fraction of 50% of AlN photocurable printing ceramic slurry was prepared, and the proportions of other additives were the same as in Example 1. The resin formula used dioctyl phthalate, 1,6-hexanediol diacrylate and ethoxylated pentaerythritol tetraacrylate in a ratio of 5:3:2. Figure 4 As shown, it is difficult to achieve a high curing depth at a low exposure intensity and to achieve effective photocuring with the AlN paste using this resin formulation.
[0062] Comparative Example 4
[0063] The relationship between the curing depth and the exposure energy was tested by using other different resin formulas. A slurry with a mass fraction of 50% of AlN photocurable printing ceramic slurry was prepared, and the proportions of other additives were the same as in Example 1. The resin formula used a ratio of 1,6-hexanediol diacrylate to ethoxylated pentaerythritol tetraacrylate of 6:4. Figure 5As shown, it is difficult to achieve a high curing depth at a low exposure intensity and to achieve effective photocuring with the AlN paste using this resin formulation.
[0064] Comparative Example 5
[0065] The relationship between the curing depth and the exposure energy was tested by using other different resin formulas. A slurry with a mass fraction of 50% of AlN photocuring printing ceramic slurry was prepared, and the proportions of other additives were the same as in Example 1. The resin formula used 1,6-hexanediol diacrylate and o-phenylphenoxyethyl acrylate in a ratio of 6:4. Figure 6 As shown, it is difficult to achieve a high curing depth at a low exposure intensity and to achieve effective photocuring with the AlN paste using this resin formulation.
[0066] Comparative Example 6
[0067] The relationship between the curing depth and the exposure energy was tested by using other different resin formulas. A slurry with a mass fraction of 50% of AlN photocuring printing ceramic slurry was prepared, and the proportions of other additives were the same as in Example 1. The resin formula used o-phenylphenoxyethyl acrylate and ethoxylated pentaerythritol tetraacrylate in a ratio of 6:4. Figure 7 As shown, it is difficult to achieve a high curing depth at a low exposure intensity and to achieve effective photocuring with the AlN paste using this resin formulation.
[0068] Comparative Example 7
[0069] The difference from Example 1 is that the sintering temperature is set to 1800°C. Fig.12 The SEM test results show that there are many pores and defects inside the sample after sintering at 1800℃.
[0070] and Fig.11 contrast, Fig.12 The density and microstructure of the samples were poor, and no well-bonded AlN porous structure ceramic sintered samples were obtained, highlighting the importance of numerical proportion formula and controlling the sintering temperature.
[0071] Table 2
[0072]
[0073]
[0074] Figure 8 and Fig. 9 This is a comparison chart of the viscosity of the slurry after mixing in Experimental Example 1 and the slurry after mixing in Comparative Examples 1, 2, 3, 4, 5, and 6. It can be clearly seen that the viscosity of Experimental Example 1 is much lower than the viscosity of Comparative Examples 1, 2, 3, 4, 5, and 6.
[0075] In summary, the present invention adopts a new resin formula to prepare the photocuring printing slurry, which can significantly improve the curing depth of the photocuring 3D printing AlN-based ceramic slurry. It is conducive to printing ultra-thin and precise AlN-based ceramic blanks for electrostatic chucks. Furthermore, the present invention flexibly controls the particle size of the powder system through processes such as ball milling and sieving, combined with the reasonable choice of sintering temperature, to obtain a complete porous structure AlN ceramic for electrostatic chucks.
[0076] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing AlN-based ultra-thin precision porous structure ceramics by photocuring 3D printing, characterized in that: include, Preparing aluminum nitride photocurable slurry, wherein the aluminum nitride ceramic slurry comprises aluminum nitride powder, photocurable resin, dispersant, photoinitiator, sintering aid and defoamer; Wherein, calculated by mass percentage, aluminum nitride powder is 50% to 73%, photocurable resin is 20% to 30%, dispersant is 1% to 5%, photoinitiator is 2% to 5%, sintering aid is 3% to 8%, and defoamer is 1% to 2%; The above-mentioned aluminum nitride photocurable slurry is added into the slurry chamber of a multi-material photocurable 3D printer, and the model information of the aluminum nitride porous ceramic skeleton is input into the printer for photocurable printing. After degreasing, decarburization and sintering, the photocurable 3D printed AlN-based ultra-thin precision porous structure ceramics are obtained.
2. The optical preparation method according to claim 1, characterized in that: The photocurable resin is a mixture of monofunctional photocurable monomers, difunctional photocurable monomers, tetrafunctional photocurable monomers and high refractive index photocurable monomers; wherein the volume ratio of the monofunctional photocurable monomers, difunctional photocurable monomers and tetrafunctional photocurable monomers is 5:3:
2.
3. The optical preparation method according to claim 2, characterized in that: The monofunctional photocurable monomer is o-phenylphenoxyethyl acrylate; the difunctional photocurable monomer is 1,6-hexanediol diacrylate; and the tetrafunctional photocurable monomer is ethoxylated pentaerythritol tetraacrylate.
4. The optical preparation method according to claim 1, characterized in that: The dispersant is a polymer copolymer dispersant, the defoamer is defoamer 204, the photoinitiator is bis(2,4,6-trimethylbenzoyl)diphenylphosphine oxide, and the sintering aid is yttrium trioxide powder.
5. The preparation method according to claim 4, characterized in that: The preparation method of the aluminum nitride slurry comprises the following steps: adding anhydrous ethanol to aluminum nitride powder, a photocurable resin, a dispersant, a photoinitiator, a sintering aid and a defoaming agent and placing the mixture in a ball mill; using zirconium oxide ball milling beads as ball milling media; mixing the mixture by ball milling and placing the mixture in a drying box for drying; and grinding the mixture through a 100-mesh sieve to obtain a mixed powder with an average particle size of 2.5 μm.
6. The preparation method according to claim 5, characterized in that: The aluminum nitride powder and the sintering aid yttrium oxide powder are mixed in a ratio of 95:
5.
7. The preparation method according to claim 5, characterized in that: The predetermined rotation speed of the ball mill is 350 rpm, the predetermined time of the ball mill is 10 h±0.5 h; the predetermined temperature of the drying box is 80° C.; the predetermined time of the drying box is 6 h; the average particle size of the aluminum nitride powder is 1.8 to 2 μm, and the average particle size of the yttrium oxide powder is 50 nm.
8. The preparation method according to claim 1, characterized in that: The aluminum nitride porous structure ceramic embryo degreasing process adopts a protective atmosphere, and the protective atmosphere adopts nitrogen; the aluminum nitride porous structure ceramic embryo is placed in a central ring tube furnace, the degreasing temperature is from 25°C to 600°C, the heating rate is 0.1°C / min to 1°C / min, and the temperature is kept at 150°C, 250°C, 350°C and 450°C for 60 to 240 minutes respectively; The exposure intensity of the photocuring printing process is 30mW / cm 2 ; Printing layer thickness is 20μm; exposure time is 4s; After layer-by-layer printing, an aluminum nitride porous structure ceramic embryo is obtained.
9. The preparation method according to claim 1, characterized in that: The degreased aluminum nitride porous ceramic embryo is subjected to decarburization treatment and placed in a low-temperature muffle furnace. The decarburization temperature is from 25° C. to 700° C., the heating rate is 0.5° C. / min to 5° C. / min, and the temperature is kept at 400° C. and 700° C. for 60 minutes respectively; The high temperature sintering is pressureless sintering or gas pressure sintering; the high temperature sintering adopts a protective atmosphere, and the protective atmosphere generally adopts inert gas nitrogen; the high temperature sintering temperature is 1800-1850° C., and the heat preservation is 4-5 hours.
10. Application of the light-cured 3D printed ultra-thin precision AlN porous structure ceramics prepared by the preparation method according to claims 1 to 9 in an electrostatic chuck.
Citation Information
Patent Citations
Ceramic material for 3D printing and manufacturing method thereof
CN105645840A
Photocuring 3D printing zirconium diboride-based ultra-high-temperature ceramic slurry as well as preparation method and application thereof
CN117756535A
Aluminum nitride ceramic photocuring slurry, preparation and preparation method of high-thermal-conductivity ceramic
CN118420353A
Production of anisotropic ceramic composite material
JP1989219088A
Photocurable resin composition and method for producing the same, and method for producing photocured product
JP2023090120A
Cited By
Photocuring 3D printing-based phosphate enhanced aluminum nitride ceramic and preparation method thereof
CN121405480A